Preoperative preparation for Graves’ disease - Xu, Tianfeng; Zheng, Xun; Wei, Tao (Frontiers in Endocrinology, 2023)
Thyroidectomy is always regarded as the crucial treatment for Graves' disease, especially in cases of poor efficacy or excessive side effects of antithyroid-drugs and 131I radioiodine therapy. To decrease the incidence of hemorrhage, thyroid storms and other severe complications during the perioperative period, surgeons explore different therapies to prepare for thyroidectomy. We performed a review of preoperative preparation with a focus on the Graves' disease population. Most of the previous schemes are effective, which contributes to the smooth operation of patients, but there is no unified standard for preoperative preparation. This review aims to summarize the preoperative preparation of Graves' disease and the latest developments. Prospective studies with longer follow up-up periods are required to select appropriate preoperative regimens based on personal thyroid statements and to identify target populations of benefit.